Existentialist Dimensions in Four Nigerian Oral Traditions and Selected Plays of Wole Soyinka - Abamba, Prince Oghenerhoro (2015)
The study examined the concept of Existentialism in some Nigerian oral cultures and analyzed four selected plays of Wole Soyinka. It further determined the representation of Existentialist thought borrowed from African oral tradition in Soyinka's plays studied. This was with a view to demonstrating the relevance of Existentialist thought in Nigerian orature and literature. The research was fieldwork and library based. The fieldwork entailed interviews with specialists in the oral traditions of Yoruba, Edo, Urhobo and Okpameri cultures who were purposively selected for the study. For the Yoruba oral tradition, a specialist in Ifa literary corpus was interviewed. One specialist each in the history and culture of Edo, Urhobo and Okpameri was interviewed. The selection method of specialists was purposive. The library work involved a review of European Existentialism in Philosophy and Literature: an analysis of Existentialist thought by some Nigerian philosophers; and an Existentialist reading of Wole Soyinka's A Dance of the Forest, The Road, Madmen and Specialists and Death and the King's Horseman. The results proved that Yoruba, Edo, Urhobo and Okpameri cultures were rich in Existentialist thought. Existentialist ideas such as being and absurdity, the irony of free will, anxiety, dread and death, and the ontological aloneness of the individual human being, were found in the myths, legends, folklore and socio-philosophical poetry of the various cultures. It was also found that much of the Existentialist material Soyinka used in the selected plays was sourced from his own Yoruba culture. A Dance of the Forest explored in depth the irony of free will; The Road and Madmen and Specialists thematized the absurdity and meaninglessness of life; while Death and the King's Horseman dramatized the theme of anxiety, dread and death, and the ontological aloneness of humans as individuals. The findings revealed that problems of existence were universal. However, in African Existentialism, the individual's acceptance of challenge and the qualities of resilience and determination negated the despair and nihilism that characterised much of European Existentialist literature. The study concluded that using Existentialist concepts to explicate the selected plays of Soyinka yielded new and emerging insights such as the irony of free will, the absurdity and futility of life and the ontological aloneness of humanity as individuals.